HOMEWORK IN ELEMENTARY SCHOOLS - Tolipova Asalxon; Mamasoliyeva Fotimaxon; G'ofurov Iqboljon (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: In this article, the authors aim at identifying the evolution and implementation of homework in last centuries, its precise advantages and disadvantages, the results taken from studies and feasible solutions to the problem of a student being reluctant to do hometasks, tips and games to make all learners engaged and interested in completing their home assignments.